2009
DOI: 10.1021/jm900519b
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Structure−Activity Relationships of Benzophenone-Based Tetraamides as Novel Antibacterial Agents

Abstract: The increase in the incidence of both hospital- and community-acquired antibiotic-resistant infections is a major concern to the healthcare community. There have been only two new classes of antibiotics approved by the FDA over the past 40 years, and clearly there is a growing need for additional antimicrobial agents. In this paper, we present our work on the discovery of a class of benzophenone containing compounds that possess good activity against MRSA, VISA, VRSA, and VRE and moderate activity against E. c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(55 citation statements)
references
References 42 publications
(137 reference statements)
3
52
0
Order By: Relevance
“…Some natural xanthones are described as important anti-staphylococcal agents, including for resistant strains, having MIC values ranging from 8 until 1.95 µg/mL. 10,[33][34][35] Thus, some of the semi synthetic ω-aminoalkoxylxanthones presented herein are potential antimicrobials and can be considered relevant specially taking into account the growing problem of resistant S. aureus strains. 1 Studies have reported the synthesis and cytotoxic activity of bromoalkoxyxanthones 30 and xanthones with nitrogenated side chains 27,28 including arylhydrazones, 36 with promising results, showing IC 50 values between 2 and 30 µM.…”
Section: Resultsmentioning
confidence: 99%
“…Some natural xanthones are described as important anti-staphylococcal agents, including for resistant strains, having MIC values ranging from 8 until 1.95 µg/mL. 10,[33][34][35] Thus, some of the semi synthetic ω-aminoalkoxylxanthones presented herein are potential antimicrobials and can be considered relevant specially taking into account the growing problem of resistant S. aureus strains. 1 Studies have reported the synthesis and cytotoxic activity of bromoalkoxyxanthones 30 and xanthones with nitrogenated side chains 27,28 including arylhydrazones, 36 with promising results, showing IC 50 values between 2 and 30 µM.…”
Section: Resultsmentioning
confidence: 99%
“…Literature evidence for benzophenone-based tetraamide compounds also showed that positive charge is a necessary requirement for selective interaction with bacterial over mammalian membranes [11]. Thus, cationic compounds are strongly attracted by electrostatic interactions to bacterial over mammalian membranes, and this characteristic is used in drug design in order to increase selectivity of antibacterial agents.…”
Section: Introductionmentioning
confidence: 99%
“…The present report describes the synthesis of nine new amidine derivatives (9)(10)(11)(12)(13)(14)(15)(16)(17) and evaluation of antibacterial activity of 27 amidine derivatives from 3,4-ethylenedioxythiophene class (including 18 previously synthesized analogues). The structure-activity relationship of their antibacterial potencies and DNA binding affinities is examined.…”
Section: Introductionmentioning
confidence: 99%
“…CAD-based MS n techniques have been applied to the characterization of unknown substances in many fields, including the pharmaceutical industry [19,20], and research on chemical warfare agents [21], proteins [22], volatile organic compounds [23], airborne oxidants [24], bacteria, DNA [25,26], and microextracted water samples [27]. Hydrogen/deuterium (H/D) exchange experiments [28][29][30] and molecular orbital calculations [31,32] have facilitated the differentiation of isomeric compounds.…”
Section: Introductionmentioning
confidence: 99%